KARAKTERISTIK BENTANG ALAM DAERAH PAYAKUMBUH, SUMATERA BARAT - Ungkap M.Lumbanbatu (Jurnal Geologi dan Sumberdaya Mineral, 2008)
The landscape of Payakumbuh and the surrounding area is characterized by the influences of volcanic and tectonic origins as well as by geological processes like weathering, erosion, sedimentation and solution. The landscape which is built up by the product of Marapi and Malintang Volcanoes, occupies the central part of the investigated area. The landscape of volcanic origin was then affected by tectonic activities producing lineaments that are assumed as active faults. These faults which are in NW-SE direction, seem to have the same direction as the Takung River Fault Zone. Based on its geomorphological characteristics and processes, the landform of the investigated area can be distinguished into volcanic, fluvial, fluvio-volcanic, denudational, structural and karst origin. It can be concluded that morfogeneticly the investigated area has been formed by endogen and exogen prosesses. Exogen prossesses produced the denudational, fluvial, and kars origin, while endogen process produced the structural and volcanic origins. Keywords: landscape, landform, volcano-tectonic origin, structural origin.